MANAGEMENT OF ENTRY AND OUTCOMES OF GENERAL SUB-SECTIONS OF EMPLOYMENT AND LEGAL AT THE EDUCATION OFFICE OF SOUTH SULAWESI - Khaeriyah Khaeriyah; Indriati Amirullah; Anne Abdul Rahman; Nurasia Natsir; Nurmadhani Fitri Suyuthi (Journal of Management and Informatics, 2022)
This research was conducted with the intention of discovering how the management of incoming and outgoing letters is handled in the General, Personnel, and Legal Subdivisions of the Office of the Education Office of the Province of South Sulawesi. This is a qualitative study, with data obtained from direct observations and interviews about the management of incoming letters and letters. The descriptive research methodology was utilized for this study's research design. Field studies by observation (observation) and interviews were used to collect data for this study (interview). The study's findings revealed that the management of incoming and outgoing letters in the General, Personnel, and Legal Subdivisions at the South Sulawesi Province Education Office, based on the results of interviews and observations, employs a combined principle, namely the principles of centralization and decentralization. In terms of archive storage, inactive archives are managed by Archivists, whereas active archives are managed by their respective subsections.